A Rapid Method for Quantifying Chlorogenic Acid Levels in Potato Samples. (27th November 2019) - Weidel, Elisabeth; Schantz, Markus; Richling, Elke
Abstract: Chlorogenic acids (CGA) are found in many plant-derived foodstuffs and are claimed to have various beneficial effects on human health. Potatoes are a major component of the human diet and contain CGA, but little is known about their abundance in these important tubers. We therefore used a rapid, sensitive, and selective method for quantifying CGAs in food using ultra-high performance LC diode array detection (UHPLC-DAD). We also established an optimized sample preparation protocol based on ultrafiltration and used these techniques to quantify the CGA contents of selected potato varieties (fresh and after storage) and potato products. The measured CGA concentrations in potato skins were 37–636 mg/100 g dry weight (DW) and were three to four times greater than those in the flesh. Storage reduced the CGA levels in potatoes by up to 81%. The studied potato purees contained 4–11 mg CGA/100 g DW. In addition, the quinic acid contents of potato flesh (11–95 mg/100 g DW) and puree (11–22 mg/100 g DW) were measured using stable isotope dilution analysis. None of the tested samples contained caffeic acid. Overall, our results demonstrated that the UHPLC-DAD method can be used to rapidly quantify CGA levels in potatoes and related food products.